PERLINDUNGAN HUKUM BAGI PEMBERI PINJAMAN ATAS RISIKO KREDIT DALAM PELAKSANAAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI (PEER TO PEER LENDING) - Indah Kusuma Wardhani; Fawzia Apriandini (Universitas Suryakancana, 2020)
The fastest growing financial technology (fintech) in Indonesia is peer to peer lending, where customers could obtain loans in a simple, easy, and fast way, yet without collateral. However, in practice, peer to peer lending has a very high credit risk because the ability of fintech companies in assessing prospective loan recipients is not as good as other financial institutions. Therefore, preventive and repressive legal protection are needed, especially for lenders, which are regulated in OJK Regulation Number 77/POJK.01/2016 concerning the Implementation of Information Technology-Based Lending and Borrowing and OJK Regulation Number 1/POJK.07/2013 concerning Consumers’ Protection in Financial Services Sector. With the two OJK Regulations, lenders have received sufficient legal protection, but it must be further strengthened, especially in terms of credit risk mitigation.Keywords: Legal Protection for Lenders, Peer To Peer Lending, Credit Risk